0639 Long Term Oral Appliance Therapy Decreases Stress Symptoms In Upper Airway Resistance Syndrome Patients. (27th May 2020) - Godoy, L B; Sousa, K M; Palombini, L O; Guimarães, T M; Poyares, D; Tufik, S; Togeiro, S
Abstract: Introduction: Upper Airway Resistance Syndrome (UARS) is suspected in individuals with excessive daytime sleepiness, fatigue and sleep fragmentation due to increased respiratory effort. UARS can negatively impact daytime function and decrease quality of life. Cognitive impairment in UARS patients has not been well stablished yet. The objective of the study was to evaluate the long-term effects of a mandibular advancement device (MAD) on cognitive function in patients with UARS compared with placebo. Methods: This study was a randomized placebo-controlled clinical trial. Thirty UARS patients were randomized in two groups: placebo and MAD groups. UARS criteria were the presence of sleepiness (Epworth Sleepiness Scale ≥ 10) and/or fatigue (Modified Fatigue Impact Scale ≥ 38) associated with an apnea/hypopnea index (AHI) ≤ 5 and a respiratory disturbance index (RDI) > 5 events/hour of sleep, and/or flow limitation in more than 30% of total sleep time. All patients completed the Rey Auditory-Verbal Learning Test (RAVLT), the Logical Memory Test, the Stroop Color Test, the Trail Making Test, the Digit Symbol Substitution Test and Inventory of Stress Symptoms (Lipp test). Cognition protocol was defined based on most used neuropsychological tests in the literature. Evaluations were performed before and after 1.5 years of treatment. Results: There was no statistically significant difference in RAVLT, Logical Memory Test, Stroop Color Test, Trail Making Test, Digit Symbol Substitution Test before and after 1.5 year of treatment in both groups. The Lipp test score decreased at alarm phase (p = 0.05) and at resistance phase (p = 0.01) after 1.5 year of MAD treatment compared to placebo. Conclusion: Mandibular advancement device was effective in decreasing stress symptoms in alarm and resistance phases of Lipp test in UARS patients after 1.5-years of MAD treatment. Support: The authors would like to thank for the support by grants from Associação Fundo de Incentivo a Pesquisa (AFIP), Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES).